Acupuncture Alleviates Menstrual Pain in Rat Model via Suppressing Eotaxin/CCR3 Axis to Weak EOS-MC Activation. (13th January 2022) - Yu, Wen-Yan; Ma, Liang-Xiao; Tian, Yuan; Mu, Jie-Dan; Zhang, Zhou; Sun, Tian-Yi; Qian, Xu; Wang, Jun-Xiang
Abstract : Introduction . Emerging data show that chemokine-mediated inflammation is involved in the occurrence and maintenance of pain. Recent evidence suggests that eotaxin levels rise when dysmenorrhea happens. The purpose of this study is to investigate whether eotaxin/CC chemokine receptor 3 (CCR3) axis, a key regulatory pathway for eosinophils (EOS) recruitment, is involved in acupuncture analgesia for dysmenorrhea. Methods . After the cold congealing dysmenorrhea (CCD) rat model prepared, animals received perpendicular needling (PN) and transverse needling (TN) at SP6, respectively, for 20 min. The CCR3 agonist CCL11 was administered 30 min prior to acupuncture. Pain behavior was assessed via a writhing response. The uterine contraction test was detected by an electrophysiological method. Eotaxin, histamine (HIS), and interleukin-6 (IL-6) levels were evaluated by ELISA. The expression of CCR3 and histamine H1 receptor (H1R) was analyzed by RT-qPCR and Western blot. The expression of EOS, mast cells (MCs), eosinophil peroxidase (EPO), and eosinophil cationic protein (ECP) was assessed by hematoxylin-eosin staining (HE), Toluidine Blue staining (TB), and immunohistochemistry, respectively. Results . Acupuncture prominently attenuated the menstrual pain in CCD rats, particularly TN technique. Electrophysiological recording data showed that the increased uterine contractility was ameliorated by acupuncture. In addition, TN decreased the release of eotaxin, HIS, IL-6, and the expression of CCR3 and H1R. HE, TB staining, and immunohistochemistry experiments showed that the increased expression of EOS, MCs, EPO, and ECP in uterine tissues was reversed by TN. Furthermore, we found that the effects of TN against CCD-induced menstrual pain, increased ECP expression, and HIS level were abolished by CCL11. Conclusion . TN alleviated menstrual pain by improving the uterine inflammatory environment via suppressing eotaxin/CCR3 axis to weak EOS-MC activation in CCD rats. The study findings support the acupuncture as a promising approach for dysmenorrhea, meanwhile, indicating the importance of performing appropriate needling technique.